Relevansi Filsafat Hukum dalam Mewujudkan Independensi Kejaksaan Republik Indonesia - Rasji; Yudha Aditya Pradana (CV Rewang Rencang, 2024)
The independence of the Attorney General's Office of the Republic of Indonesia is a fundamental factor in realizing a fair and free justice system from external intervention. However, in practice, many obstacles are faced, including how to apply legal philosophy in the policies and institutional practices of the Attorney General's Office to maintain its independence and how relevant legal philosophy is in realizing the independence of the Attorney General's Office of the Republic of Indonesia. The research method used is normative legal research sourced from secondary data. The results of the study indicate that the application of legal philosophy in the institutional policies and practices of the Attorney General's Office of the Republic of Indonesia has a crucial role in maintaining its independence as a law enforcement institution. The independence of the Attorney General's Office must be realized through policy reforms that emphasize the autonomy of prosecutors in the prosecution process, strengthening internal oversight mechanisms, and increasing the integrity and professionalism of law enforcement officers. Legal philosophy has strong relevance in forming a conceptual foundation for the institutional independence of the Attorney General's Office. The Attorney General's Office must act based on law, ethics, and the interests of justice, not certain political or economic interests. Without strong independence, the Attorney General's Office risks losing credibility and becoming a tool of power.